Tata Kelola Pemilu dalam Pemenuhan Hak-Hak Pemilih Penyandang Disabilitas - Ade Rio Saputra; Jendrius Jendrius; Bakaruddin Bakaruddin (ARISTO, 2019)
This study examines electoral governance for voters with disabilities in simultaneous elections in 2015 that are still not optimal. This can be seen in the election of the Governor and Deputy Governor of West Sumatra Province in 2015 in Kabupaten Padang Pariaman. This research is a descriptive qualitative research using in-depth interview method, literature study and documentation study. The findings in this study are that election management is still not maximal towards the fulfillment of the rights of disability voters in Padang Pariaman Regency in the election of the Governor and Deputy Governor of West Sumatra Province in 2015. Rule applications are often ignored by election organizers. This can be seen from the stages of socialization that were not carried out by the election organizers in this case the Padang Pariaman Regency KPU to voters with disabilities. In addition, there are still TPS that do not have access to disability voters. This has an impact on the low number of participation of voters with disabilities in the simultaneous election in 2015. Existing regulations are not in line with the technical implementation in the field.